Genotype and nitrogen effects over maize kernel hardness and endosperm zein profiles - Gerde, Jose Arnaldo (2016)
Maize (Zea mays L.) kernel hardness is of utmost importance for dry-milling processors. Zeins, maize prolamins, are known to be key proteins affecting this trait. We investigated the response of kernel zein profiles to N fertilization in maize hybrids with contrasting kernel hardness (measured as test weight, vitreousness, kernel density, and floaters percentage). A field experiment was done during two seasons, with three N fertilization treatments and four commercial hybrids with different hardness (two flint and two dent kernel types). We also measured yield, kernel protein concentration, and zein profiles (Z2, or g and β, and Z1, or a and d). Flint kernel type always yielded less and showed higher kernel hardness indicators when compared with dents (P < 0.01). N fertilization helped increase yield and kernel hardness in both kernel types. Flint kernel type had consistently more Z2 than dents, while only in 1 yr Z1 was higher in flints. Dent kernel type had a Z1/Z2 ratio similar to or higher than flints. Increasing N resulted in increased concentration of both zein types, but the effect was more pronounced on Z1. Significant correlations were observed between the different zein types (Z1 and Z2) and hardness indicators and total protein concentration, but Z2 showed the highest correlations with all kernel hardness traits. Our results expand previous knowledge on genotype and N fertilization effects over zein profiles and their involvement in kernel physical characteristics relevant for dry milling.